2009
DOI: 10.1186/1477-7819-7-25
|View full text |Cite
|
Sign up to set email alerts
|

Lymphangiosis carcinomatosa in squamous cell carcinomas of larynx and hypopharynx – value of conventional evaluation and additional immunohistochemical staining of D2-40

Abstract: Background: Recent studies revealed a predictive value of lymphatic vessel invasion (L1) for the nodal metastasizing and poor prognosis in malignant tumors at different sites. The monoclonal antibody D2-40 (podoplanin) stains specifically endothelial cells of lymphatic vessels and improves the search for L1. However, the importance of this immunohistochemical staining was not investigated in squamous cell carcinomas (SCC) of larynx and hypopharynx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Recent studies identified podoplanin as a potential predictor of lymphatic dissemination in OSCC [1,23,25,26]. Podoplanin is a mucin-type transmembrane glycoprotein that is specifically expressed in lymphatic endothelial cells but not in blood endothelial cells [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies identified podoplanin as a potential predictor of lymphatic dissemination in OSCC [1,23,25,26]. Podoplanin is a mucin-type transmembrane glycoprotein that is specifically expressed in lymphatic endothelial cells but not in blood endothelial cells [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Podoplanin is a glycoprotein that is recognized by the monoclonal antibody D2–40, which is considered the most reliable marker of lymphangiogenesis . Zhao et al examined podoplanin expression in OSCC and reported the proliferation of intratumoral and peritumoral lymphatics, suggesting that the spread of metastatic cells also occurs via intratumoral vessels.…”
Section: Discussionmentioning
confidence: 99%
“…44 Podoplanin is a glycoprotein that is recognized by the monoclonal antibody D2-40, which is considered the most reliable marker of lymphangiogenesis. 14,17,18,22,23,26,45 Zhao et al 26 examined podoplanin expression in OSCC and reported the proliferation of intratumoral and peritumoral lymphatics, suggesting that the spread of metastatic cells also occurs via intratumoral vessels. Jin et al 46 have argued that the intratumoral region contains no functional lymphatic vessels and that lymphatic vessels in the tumor margin facilitate dissemination of tumor cells in non-small cell lung cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations